A cosmic window on the dark axion portal - Heejoung Hong; Ui Min; Minho Son; Tevong You (Journal of High Energy Physics, 2024)
Abstract Axions and dark photons are common in many extensions of the Standard Model. The dark axion portal — an axion coupling to the dark photon and photon — can significantly modify their phenomenology. We study the cosmological constraints on the dark axion portal from Cosmic Microwave Background (CMB) bounds on the energy density of dark radiation, ∆N eff. By computing the axion-photon-dark photon collision terms and solving the Boltzmann equations including their effects, we find that light axions are generally more constrained by ∆N eff than from supernova cooling or collider experiments. However, with dark photons at the MeV scale, a window of parameter space is opened up above the supernova limits and below the experimental exclusion, allowing for axion decay constants as low as f a ~ 104 GeV. This region also modifies indirectly the neutrino energy density, thus relaxing the cosmological upper bound on the sum of neutrino masses. Future CMB measurements could detect a signal or close this open window on the dark axion portal.